(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2013)
لا شك أن موضوع المرأة أصبح ركناً أساساً في الحياة العامة لكافة المجتمعات باختلاف عاداتها وتقاليدها ومفاهيمها ومنبرًا مهماً في مجال الأبحاث والدراسات والمؤتمرات الدولية. فالمرأة نصف المجتمع وسبب وجود النصف الآخر وإبداعه ولديها طاقات هائلة إن لم تستغل ستهدر و يحرم المجتمع منها، وحرمانه منها يعني تبديد للنمو الاقتصادي والذي بدوره يضعف التنمية الاقتصادية للبلد. يتمحور موضوع بحث تمكين المرأة وعلاقته بعدد الأولاد حول بيان ماهية تمكين المرأة من خلال مجالات، وأهمية ومظاهر تمكين المرأة وذلك لأهمية المرأة كونها الأساس في تشكيل الأسرة والمجتمع، وهي بذلك تعد من أهم عناصر المجتمع وتنميته، كما تم في هذا البحث ذكر مؤشرات تمكين المرأة، وبعض معوقات هذا التمكينن والآثار المترتبة على ذلك ليأتي البحث على واقع تمكين المرأة السورية وأثر ذلك على عدد الأولاد في الأسرة بناء على عدد من المتغيرات التي تم اختيارها. توصلت الدراسة إلى وجود ارتباط سالب(عكسي) ذي دلالة إحصائية للمتغيرات(المستوى التعليمي للزوجة، والعمر عند الزواج الأول) في عدد الأولاد، في حين ظهر أثر سلبي لمتغير العمل في مستوى القطاع العام ليس له دلالة إحصائية في عدد الأولاد، كما توصلت إلى وجود ارتباط موجب(طردي) ذي دلاله إحصائية للمتغيرات(العمر الحالي للمرأة، واستخدام وسائل تنظيم الأسرة) في عدد الأولاد. ومن ثم أصبح ممكناً عرض مفصل للنتائج و تحديد للتوصيات التي توصلت إليها الباحثة وأخيراً عرض للمصادر التي اعتمدت لأغراض البحث There is no doubt that the subject of women has become a cornerstone in the public life of all societies, with all their different customs, traditions and concepts. It has also become an important platform for research, studies and international conferences. Women, one half of a society, and the cause of the other half’s existence, have huge potentials which will be wasted and unless exploited well. This leads to squandering economic growth which, in turn, weakens the country’s economic development. The topic of empowering of women and its relationship to the number of children is about defining the empowerment of women in certain areas and its importance in being the basis for the formation of the family and society. Under this research there is one of the most important elements of society and its development, with women’s empowerment indicators and some obstacles to empowerment and implications of research on reality comes the empowerment of women and the impact on the number of children in the family based on a number of variables that have been selected. This study found a statistically significant negative correlation (reverse) of the variables of the educational level of wife and age at first marriage to the number of children, while there was a negative impact of the work in the public sector variable with no statistical significance in the number of children. The study also found a statistically significant positive correlation (directly proportional) of the variables of current age for women and family planning usage to the number of children. It has become possible to make a detailed presentation of the results and recommendations reached by the researcher and finally display the resources for this research.